InGaN multiquantum wells—problem of carrier injection - Agata Bojarska-Cieślińska; Łucja Marona; Szymon Grzanka; Ewa Grzanka; Piotr Perlin (Scientific Reports)
Abstract This study addresses the issue of effective carrier injection to quantum wells in laser diode structures. The nitride light emitting structures used in this study were fabricated by Metal-Organic Vapor Phase Epitaxy (MOVPE). We developed three distinct sets of samples, with varying quantum barrier thickness, different QWs indium composition and different position relative to the p- and n-sides of the structure. Electroluminescence (EL) and cathodoluminescence (CL) spectra, together with nextnano simulations, were analyzed to investigate the impact of these structural variations on device performance. Our findings revealed that the thickness of the quantum barriers significantly affects the carrier transport and recombination efficiency. Thicker barriers impede hole transport to the quantum wells (QWs). As a result, light emission is predominantly from the QWs located closer to the p-GaN layer. However, in a well-optimized active region the carrier distribution is uniform, leading to both QWs emitting similar amount of light. We also investigated how different indium compositions in the QWs affect the energy levels and recombination dynamics. Our study showed that in structures with two QWs of different indium content, a small (less than 2%) difference in indium concentration leads to uniform light emission across the wells, while a larger difference concentrates recombination in the deeper well.